Mediational strategies in a dynamic assessment approach to L2 listening comprehension: Different ability levels in focus - Izadi, Mehri; Khoshsima, Hooshang; Nourmohammadi, Esmaeel; Yarahmadzehi, Nahid (Italian Sociological Review, 2018)
The present study is an attempt to shed light on the mediator-learner’s interaction in the development of listening comprehension skill and compare this interaction between high and low proficient L2 learners of English. 30 L2 learners participated in Oxford’s Quick Placemat Test and the Interactions/Mosaic Listening Placement Test to select those whose proficiency levels and listening skills were based on the placement guide of the tests, at upper-intermediate and advanced levels. Out of 30 students, 12 learners (advanced level=6, upper-intermediate=6) volunteered to participate in individualized tutoring sessions. Learners listened to the listening items and answered the item(s) individually. Upon the learner’s failure to answer the item, the mediator intervened and provided mediation. Mediation was provided using the interactionist approach. The qualitative data were then coded in terms of task completion along with errors and struggles to indicate the quantity and quality of mediation happened throughout the Dynamic Assessment (DA) intervention. Qualitative comparisons were made between the two ability levels on the type of mediation required at these two ability levels. Quantitative comparisons were made to find out learners’ Zone of Actual Development (ZAD), Zone of Proximal Development (ZPD), Gain Score (GS), and Learning Potential Score (LPS). Findings of the study revealed that DA mediation resulted in the development of the listening comprehension ability of advanced and upper-intermediate learners. The ability level of the learners was not, however, a determining factor in enhancing the development of the listening comprehension ability of learners at two ability levels. A close qualitative analysis of all the mediated interactions revealed that twenty-five mediational strategies were identified that promoted the development of listening abilities of advanced and upper-intermediate level learners. It is also revealed that the upper-intermediate learners required more mediational support as compared to the advanced learners.